Application of deep eutectic solvents for the determination of inorganic analytes - Vasil Andruch; Viera Vojteková; Alina Kalyniukova; Gokhan Zengin; Ingrid Hagarová; Tanya Yordanova (Advances in Sample Preparation)
Deep eutectic solvents (DESs), due to their unique physicochemical properties, such as low volatility, tunable viscosity, and excellent solvation capabilities, have emerged as promising alternatives to conventional solvents in the determination of inorganic analytes. This work comprises various DES compositions that effectively improve the sensitivity, selectivity, and environmental sustainability of analytical procedures for the determination of inorganic analytes. DESs crucially take part in extraction, preconcentration, and digestion processes, followed by measurements with atomic absorption spectrometry, plasma-based techniques, UV–Vis spectrophotometry, etc. This work aims to reveal their great potential in the field of elemental analysis for the determination of inorganic analytes in various types of samples. Furthermore, the challenges and limitations associated with the use of DESs, including matrix effects, viscosity issues and compatibility with analytical instrumentation, are critically evaluated.